Growth arrest-specific 6 as a predictor of gastroesophageal varices in patients with liver cirrhosis - Khaled A.-A Eid; Mona M Abdelmeguid; Muhammad Abdel-Gawad; Amera A.N Kotb (Wolters Kluwer Medknow Publications, 2021)
Background and aim Early detection of patients with gastroesophageal varices at high risk of bleeding is crucial. Nevertheless, sparing endoscopy to low-risk patients would be of value. Therefore, noninvasive methods have been proposed. Our study aimed to verify whether plasma GAS6 concentrations are related to the presence and/or degree of esophageal varices in patients with LC. Patients and methods This cross-sectional study included 100 patients with LC who underwent upper gastrointestinal endoscopy. Results Mean level of GAS6 was 77.70±21.31 among enrolled patients. Patients with varices had significantly higher level of GAS6 in comparison with those without varices (82.93±18.12 vs. 45.57±4.18 ng/ml; P<0.001). Level of serum GAS6 was also increased with advancement in the variceal grade. Conclusion Plasma level of GAS6 was higher among patients having varices in comparison with those without, and its level was increased with advancement in the grade of varices. GAS6 is reported to have a good predictive value for hepatic fibrosis in patients with chronic liver disease.